Macroeconomic Impact of Pension System Upon Private Pension Funds Scheme. Empirical Evidence From Central and Eastern European Countries - Dumiter, Florin Cornel; Jimon, Ștefania Amalia; Balteș, Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The significance of retirement savings and private pension funds increased in the latest decades and gathered important amounts of capitals. The purpose of this paper is to investigate the macroeconomic effects of pension systems from an investment perspective in five Central and Eastern European countries. The analyzing process regarding several underlying macroeconomic effects of pension systems started from the premises that there is a strong connection between the structure of pension systems, the national economy and the development of the financial sector. The econometric tests were processed and applied by using pool data regression models and the method Pooled Instrumental Variables (IV) - Two-stage Least Squares (2SLS). The main conclusion highlights that the interest rate at deposits is correlated with the amount of incomes earned by population, inflation rate, severe material deprivation rate and the investment strategy of private pension funds.